'Cellulomonas timonensis' sp. nov., taxonogenomics description of a new bacterial species isolated from human gut. (May 2018) - Ndongo, S.; Bittar, F.; Beye, M.; Robert, C.; Di Pinto, F.; Fournier, P.-E.; Raoult, D.; Lagier, J.-C.
Abstract: 'Cellulomonas timonensis' sp. nov. strain sn7 T is a new species within the Cellulomonas genus. We present the main phenotypic characteristics and provide a complete annotation of its genome sequence. This facultative anaerobic bacterium, isolated from the stool of 38-year-old obese Frenchman, is Gram-positive, has motile rods and is sporulating. The genome is 4 057 828 bp long with 72.42% G + C content. Of the 3732 predicted genes, 3667 were protein-coding genes and 65 were RNAs.